2018
DOI: 10.21873/anticanres.12644
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Transformation in Mature Cystic Teratomas of the Ovary: Case Reports and Review of the Literature

Abstract: Malignant transformation occurs in 1.5-2% of mature cystic teratomas (MCT)s of the ovary and usually consists of squamous cell carcinoma, whereas other malignancies are less common. Diagnosis and treatment represent a challenge for gynecologic oncologists. The preoperative detection is very difficult and the diagnostic accuracy of imaging examinations is uncertain. The tumor is usually detected post-operatively based on histopathologic findings. This paper reviewed 206 consecutive patients who underwent surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…75 Moreover, although mature cystic teratoma hardly undergoes malignant transformation, the possibility of such incidence increases with age. [76][77][78] Overall, the close relations between ovarian benign lesions and carcinoma incidences highlight the importance of study of benign lesion microenvironment. Our results indicated that different ovarian benign lesions have undergone significant alterations according to their pathological states, with highest variations in their ECM elasticity most probably due to cell remodeling which affects ECM synthesis and regulation.…”
Section: Dovepressmentioning
confidence: 99%
“…75 Moreover, although mature cystic teratoma hardly undergoes malignant transformation, the possibility of such incidence increases with age. [76][77][78] Overall, the close relations between ovarian benign lesions and carcinoma incidences highlight the importance of study of benign lesion microenvironment. Our results indicated that different ovarian benign lesions have undergone significant alterations according to their pathological states, with highest variations in their ECM elasticity most probably due to cell remodeling which affects ECM synthesis and regulation.…”
Section: Dovepressmentioning
confidence: 99%
“…Struma ovarii is a rare monodermal ovarian teratoma which contains at least 50% of thyroid tissue: its prevalence among all ovarian tumors is 0.3-1% ( 6) and 2% among mature cystic teratomas (7). Malignant mature cystic teratoma transformation has been reported in 5-10% of cases, while metastasis can develop in about 5-23% of malignant mature cystic teratomas (8). If the mass is big patients may suffer from abdominal pain or constipation, but strumal carcinoids are sometimes just incidental findings.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Mature cystic teratomas of the ovary have an incidence of approximately 1.2-14.2 cases per 100.000 women per year, accounting for 60% of all benign ovarian tumors, and may occur at any age, with the highest peak between 30 and 40 years (1,2). These ovarian germ cell tumors undergo malignant transformation in approximately 2% of the cases, and squamous cell carcinoma is the most commonly associated cancer (1,3,4). Less frequently encountered neoplasias are represented by mucinous carcinomas (5,6), thyroid carcinomas (3,(5)(6)(7)(8)(9), carcinoids (5,10), neuroectodermal tumors (11,12) and sarcomas (13).…”
mentioning
confidence: 99%
“…These ovarian germ cell tumors undergo malignant transformation in approximately 2% of the cases, and squamous cell carcinoma is the most commonly associated cancer (1,3,4). Less frequently encountered neoplasias are represented by mucinous carcinomas (5,6), thyroid carcinomas (3,(5)(6)(7)(8)(9), carcinoids (5,10), neuroectodermal tumors (11,12) and sarcomas (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation